Mesenchymal Stromal Cell-Derived Extracellular Vesicles Attenuate Dendritic Cell Maturation and Function - Reis, Monica; Mavin, Emily; Nicholson, Lindsay; Green, Kile; Dickinson, Anne M.; Wang, Xiao-nong (Frontiers in Immunology, 2018)
Mesenchymal stromal cells (MSCs) are potent regulators of immune responses largely through paracrine signaling. MSC secreted extracellular vesicles (MSC-EVs) are increasingly recognized as the key paracrine factors responsible for the biological and therapeutic function of MSCs. We report the first comprehensive study demonstrating the immunomodulatory effect of MSC-EVs on dendritic cell (DC) maturation and function. MSC-EVs were isolated from MSC conditioned media using differential ultracentrifugation. Human monocyte-derived DCs were generated in the absence or presence of MSC-EVs (20 ug/ml) then subjected to phenotypic and functional analysis in vitro. MSC-EV treatment impaired antigen uptake by immature DCs and halted DC maturation resulting in reduced expression of the maturation and activation markers CD83, CD38, and CD80, decreased secretion of pro-inflammatory cytokines IL-6 and IL-12p70 and increased production of anti-inflammatory cytokine TGF-β. MSC-EV treated DCs also demonstrated a diminished CCR 7 expression after LPS stimulation, coupled with a significantly reduced ability to migrate towards the CCR7-ligand CCL21, although they were still able to stimulate allogeneic T cell proliferation in vitro. Through microRNA profiling we have identified 49 microRNAs, which were significantly enriched in MSC-EVs compared to their parent MSCs. MicroRNAs with known effect on DC maturation and functions, including miR-21-5p, miR-142-3p, miR-223-3p and miR-126-3p, were detected within the top 10 most enriched miRNAs in MSC-EVs, with MiR-21-5p as the third highest expressed miRNA in MSC-EVs. In silico analysis revealed that miR-21-5p targets the CCR7 gene for degradation. To verify these observations, DCs were transfected with miR-21-5p mimics and analyzed for their ability to migrate towards the CCR7-ligand CCL21 in vitro. MiR-21-5p mimic transfected DCs showed a clear trend of reduced CCR7 expression and a significantly decreased migratory ability towards the CCL21. Our findings suggest that MSC-EVs are able to recapitulate MSC mediated DC modulation and MSC-EV enclosed microRNAs may represent a novel mechanism through which MSCs modulate DC functions. As MSCs are currently used in clinical trials to treat numerous diseases associated with immune dysregulation such as graft-versus-host disease and inflammatory bowel disease, our data provide novel evidence to inform potential future application of MSC-EVs as a cell-free therapeutic agent.